Identification of a Small Molecule Activator for AphB, a LysR-Type Virulence Transcriptional Regulator in Vibrio cholerae - Privett, Britney R. (Biochemistry, 2017)
AphB is a LysR-type transcriptional regulator (LTTR) that cooperates with a second transcriptional activator, AphA, at the tcpPH promoter to initiate expression of the virulence cascade in Vibrio cholerae. Since it is not yet known whether AphB responds to a natural ligand in V. cholerae that influences its ability to activate transcription, we used a computational approach to identify small molecules that influence its activity. In silico docking was used to identify potential ligands for AphB, and saturation transfer difference NMR was subsequently employed to access the validity of promising targets. We identified a small molecule, BP-15, that specifically binds the C-terminal regulatory domain of AphB and increases its activity. Interestingly, molecular docking predicts that BP-15 does not bind in the putative primary effector-binding pocket located at the interface of RD-I and RD-II as in other LTTRs, but rather at the dimerization interface. The information gained in this study helps us to further understand the mechanism by which transcriptional activation by AphB is regulated by suggesting that AphB has a secondary ligand binding site, as observed in other LTTRs. This study also lays the groundwork for future design of inhibitory molecules to block the V. cholerae virulence cascade, thereby preventing the devastating symptoms of cholera infection.